2012
DOI: 10.1371/journal.pone.0036826
|View full text |Cite
|
Sign up to set email alerts
|

Epicoccum nigrum P16, a Sugarcane Endophyte, Produces Antifungal Compounds and Induces Root Growth

Abstract: BackgroundSugarcane is one of the most important crops in Brazil, mainly because of its use in biofuel production. Recent studies have sought to determine the role of sugarcane endophytic microbial diversity in microorganism-plant interactions, and their biotechnological potential. Epicoccum nigrum is an important sugarcane endophytic fungus that has been associated with the biological control of phytopathogens, and the production of secondary metabolites. In spite of several studies carried out to define the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(79 citation statements)
references
References 60 publications
1
72
0
6
Order By: Relevance
“…Fusarium is a serious plant pathogen, but many non-pathogenic endophytic Fusarium isolates have been reported in the literature [24]. E. nigrum has also been described as frequently occurring endophyte, mostly detected in phylloplane environment that is in good agreement with our findings in sweet cherry (see Table 1; [11,28]). While Alternaria, Fusarium and Epicoccum were detected in roots, shoots and leaves, the presence of several other endophytes seems to be organ specific.…”
Section: Discussionsupporting
confidence: 91%
“…Fusarium is a serious plant pathogen, but many non-pathogenic endophytic Fusarium isolates have been reported in the literature [24]. E. nigrum has also been described as frequently occurring endophyte, mostly detected in phylloplane environment that is in good agreement with our findings in sweet cherry (see Table 1; [11,28]). While Alternaria, Fusarium and Epicoccum were detected in roots, shoots and leaves, the presence of several other endophytes seems to be organ specific.…”
Section: Discussionsupporting
confidence: 91%
“…Madural. In this work was additionally found a number of nonpathogenic OTUs, being some of them described in the literature as presenting the useful features of antagonism against phytopathogens, such as Chaetomium globosum (Awad et al, 2014), Epicoccum nigrum (Fávaro et al, 2012), Penicillium brevicompactum (Jackson et al, 1997) and Trichoderma koningii (Reddy et al, 2014), and/or entomopathogenecity (e.g. Aspergillus westerdijkiae; Baggio et al, 2016).…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies have also reported the potential of C. globosum and E. nigrum to reduce the growth of several phytopathogenic fungi (e.g. Aggarwal, 2015;Biswas et al, 2012;Fávaro et al, 2012;Lahlali and Hijri, 2010); however, this is the first work showing an effective antagonist activity of these two species against C. acutatum. Similarly, studies examining antagonistic effect of A. westerdijkiae against phytopathogens have never been performed, being only tested its entomopathogenic properties against Periplaneta americana (Baggio et al, 2016).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…We cannot comment at this stage on the morphospecies, but three of the fungal genera identified, Epicoccum, Trichoderma and Ulocladium, contain mycoparasitic species. Some endophytic Epicoccum species have been screened as potential biocontrol agents of fungal pathogens of diverse crops, including potato, sugarcane and stone fruits (De Cal et al 2009;Lahlali and Hijri 2010;Fávaro et al 2012); whilst Trichoderma is a well known mycoparasitic genus that has been widely used for biocontrol of plant pathogens (Harman 2000; Holmes et al 2004)). Similarly, some Ulocladium species have also generated interest as mycoparasites of plant pathogens, and Kohl et al (1997) reported that Ulocladium atrum is antagonistic to Botrytis disease in onions.…”
Section: Fig 2 Continuedmentioning
confidence: 99%